A dual harmonic balanced configuration transformer with harmonic multi-port isolation: Design, modeling and analysis. (February 2023) - Tian, Ye; Luo, Longfu; Li, Yong; Liu, Qianyi; Wang, Shaoyang; Huang, Zhao; Lin, Jinjie
Highlights: Elaborating the architecture and design method of the dual harmonic balanced configuration and further obtaining the coupling characteristics under the special configuration. On this basis, by analyzing the harmonic transfer relationship, the multi-port harmonic isolation performance is demonstrated. The electromagnetic decoupling model is established and further extended and simplified to meet specific applications. With the derivation of the decoupling circuit, the essence of multi-port harmonic isolation is thoroughly revealed. The matrix transformation-based fault analysis method applicable to the established model is studied and further generalized to various faults. Abstract: This paper presents a dual harmonic balanced configuration transformer (DHBCT) carefully designed to achieve harmonic multi-port isolation in the regional hub substation. Firstly, the design and implementation of the special configuration are elaborated. Then, the magnetic field coupling characteristics expressed by the coupling inductances in the dual harmonic balanced configuration are derived and demonstrated. On this basis, the filtering mechanism of the DHBCT that can achieve harmonic multi-port isolation is demonstrated. Besides, in view of the difficulties caused by multiple windings and characterization characteristics for simulation, the electromagnetic decoupling model that can reflect the balanced configuration is established. Considering various application scenarios and the convenience of the application, the decoupling model is extended and simplified. Following that, the fault analysis is investigated using the established model. Finally, the correctness and accuracy of the proposed models and fault analysis method are verified by experiments and simulations.